Antibody potency relates to the ability to recognize the closed, pre-fusion form of HIV Env - Guttman, Miklos (Nat Commun, 2015)
HIV’s envelope glycoprotein (Env) is the sole target for neutralizing antibodies. The structures of many broadly neutralizing antibodies (bNAbs) in complex with truncated Env subunits or components have been reported. However, their interaction with the intact Env trimer, and the structural determinants that underlie neutralization resistance in this more native context are less well understood. Here we use hydrogen/deuterium-exchange to examine the interactions between a panel of bNAbs and native-like Env trimers (SOSIP.664 trimers). Highly potent bNAbs cause only localized effects at their binding interface, while the binding of less potent antibodies is associated with elaborate changes throughout the trimer. In conjunction with binding kinetics, our results suggest that poorly neutralizing antibodies can only bind when the trimer transiently samples an open state. We propose that the kinetics of such opening motions varies among isolates, with Env from neutralization-sensitive viruses opening more frequently than Env from resistant viruses.